2006
DOI: 10.1007/s10552-006-0011-0
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Studies of Alcohol and Breast Cancer with Consideration of the Methodological Issues

Abstract: Objective: To give an up-to-date assessment of the association of alcohol with female breast cancer, addressing methodological issues and shortfalls in previous overviews.Methods: Meta-analysis of studies (any language) providing original data on incidence of first primary breast cancer and alcohol. Two reviewers independently extracted data. Study quality assessed by objective criteria; funnel plots examined for publication bias. Risks associated with drinking versus not drinking and dose-response not constra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
147
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(155 citation statements)
references
References 30 publications
4
147
2
2
Order By: Relevance
“…When the dose-response effect was measured an increased risk of 10% for each 10 g of ethanol/ day (RR 1.10, 95%CI 1.05-1.15) was observed. The risk remained regardless of the type of beverage consumed (beer, wine or spirits) (Key et al, 2006). Another study, after adjustment for smoking, showed a dose-response effect with a 7% increase in the risk of developing breast cancer for each 10g/day of alcohol consumed (p<0.001) (Hamajima et al, 2002).…”
Section: Alcohol Consumption and Risk Of Breast And Female Genital Ormentioning
confidence: 97%
See 2 more Smart Citations
“…When the dose-response effect was measured an increased risk of 10% for each 10 g of ethanol/ day (RR 1.10, 95%CI 1.05-1.15) was observed. The risk remained regardless of the type of beverage consumed (beer, wine or spirits) (Key et al, 2006). Another study, after adjustment for smoking, showed a dose-response effect with a 7% increase in the risk of developing breast cancer for each 10g/day of alcohol consumed (p<0.001) (Hamajima et al, 2002).…”
Section: Alcohol Consumption and Risk Of Breast And Female Genital Ormentioning
confidence: 97%
“…Four publications were found (Table 3) evaluating the association between alcohol consumption and the risk of breast cancer (Hamajima et al, 2002;Key et al, 2006;Bagnardi et al, 2012;Seitz et al, 2012). A meta-analysis classified the articles in scores according to the degree of control for confounding.…”
Section: Alcohol Consumption and Risk Of Breast And Female Genital Ormentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Over the years, numerous epidemiological studies have shown that increased alcohol consumption and binge-drinking are dose-dependently associated with the development of human breast cancers. [3][4][5][6][7][8][9] These findings have also been recapitulated using mouse animal models, where ethanol-fed mice showed increased rates of breast cancer tumor growth. 10 Importantly, alcohol consumption also significantly…”
Section: Introductionmentioning
confidence: 92%
“…Epidemiological studies conducted mainly in Western countries have shown that alcohol consumption is associated with an increased risk of breast cancer (Hamajima et al 2002;Key et al 2006), and it is now regarded as an established breast cancer risk factor (Baan et al 2007). Among the Japanese population, however, a qualitative review of the existing evidence has indicated that the association between alcohol consumption and breast cancer risk remains inconclusive (Nagata et al 2007).…”
Section: Introductionmentioning
confidence: 99%